2018
DOI: 10.1017/s0022215118000889
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic push-through technique compared to microscopic underlay myringoplasty in anterior tympanic membrane perforations

Abstract: The endoscopic push-through technique for anterior tympanic membrane perforations is as effective as microscopic underlay myringoplasty; furthermore, it is less invasive and takes less operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 15 publications
2
29
0
2
Order By: Relevance
“…Although various grafting techniques and graft materials have been described for repairing anterior perforations of the tympanic membrane, graft uptake rates are relatively low in patients with anterior perforations of the tympanic membrane. 8,10–12 According to a recent literature review, Jalali et al . reported that cartilage graft with comparable audiometric outcomes offers a higher graft uptake rate compared with temporalis fascia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although various grafting techniques and graft materials have been described for repairing anterior perforations of the tympanic membrane, graft uptake rates are relatively low in patients with anterior perforations of the tympanic membrane. 8,10–12 According to a recent literature review, Jalali et al . reported that cartilage graft with comparable audiometric outcomes offers a higher graft uptake rate compared with temporalis fascia.…”
Section: Discussionmentioning
confidence: 99%
“…Reported graft uptake rate ranges between 84.4 and 97.4 per cent in patients who underwent endoscopic push-through myringoplasty. 4,8,13,14 Kim et al . reported a perforation closure rate of 91.3 per cent in patients undergoing modified butterfly-inlay cartilage (comprising one side perichondrium as in our study) myringoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perichondrium graft is placed directly over the surface of the tympanic membrane and annulus. Because endoscopy provides an excellent view, allowing clear observation of the entire remnant tympanic membrane and middle ear structure, 3,4,13,14 this technique does not require elevation of the tympanomeatal flap.…”
Section: Discussionmentioning
confidence: 99%
“…An endoscopic transcanal surgery is suggested to provide adequate vision without a postauricular approach or canalplasty with comparable success rates in anterior TM perforations. [28][29][30] Eren et al [28] reported a 95.5% closure rate for anterior TM perforation with an improved airbone gap from 19.3±3.3 dB to 10.8±4.5 dB in 21 of 22 patients who underwent a cartilage butterfly myringoplasty with an endoscopic transcanal approach. El-Hennawi et al [30] compared endoscopic push-through myringoplasty (28 patients) and microscopic myringoplasty (28 patients) with a tragal cartilage perichondrial graft and reported that the endoscopic technique is as effective as a microscopic approach in terms of surgical success rates with less operative time and invasiveness.…”
Section: Discussionmentioning
confidence: 99%